(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Background: Breast cancer is the most common type of cancer in women with an increasing incidence. Health professionals play an important role in reducing disability and death from breast cancer, a major public health problem. The aim: Is to determine the levels of knowledge of nurses in two hospitals in Basrah city, Iraq about breast cancer, risk factors and symptoms. Method: Cross-sectional descriptive study including nurses working in Al-Sadr Teaching Hospital and Basrah Teaching Hospital. The study sample consisted of 125 nurses who agreed to participate in the study. A personal information form and questionnaire prepared by the researchers were used to determine nurses’ knowledge levels and attitudes about risk factors and symptoms for breast cancer and breast cancer in the data collection. Results: It was determined that 82.4% of the research group were aged (20-41 years), 45.6% were married and 28.8% were university graduates. It was determined that 8% of nurses had a history of breast cancer, 13.6% had a family history of breast cancer, 31.2% did not know how to get BSE, and 60.8% did not have an annual breast examination. The averages of the respondents in the questionnaire were, respectively: (1.83 ± 0.36) (risk factors for breast cancer), (1.91 ± 0.43) (signs and symptoms of breast cancer), (2.32 ± 0.45) (methods of detection of breast cancer).